Breathable and Flexible Polymer Membranes with Mechanoresponsive Electric Resistance. (9th January 2020) - Gao, Qiang; Kopera, Bernd A. F.; Zhu, Jian; Liao, Xiaojian; Gao, Chao; Retsch, Markus; Agarwal, Seema; Greiner, Andreas
Abstract: Flexible low‐resistance membranes play an important role in soft electronics as sensors for robotics, body movement monitoring, nanogenerators to collect kinetic energy from body movements, and flexible batteries. Despite great efforts, low‐resistance, mechanically stable large‐dimensional membranes that tolerate very high deformability without sacrificing resistance produce low joule heating and allow passage of gases for human comfort are still being sought. Here, one of the solutions is provided by sandwiching a network of silver nanowires (AgNWs) between two highly porous electrospun thermoplastic polyurethane (TPU) membranes. The membranes are mechanically robust (both for bending and stretching) with a strong interface and large strain before breakage (more than 700%). The sheet resistance is as low as <0.1 (±0.01) Ω sq −1, and changed to only 1.6 (±0.43) Ω sq −1 upon stretching to 100% strain. The combination of polymer elasticity and the AgNW network structure provides a reversible change in resistance beyond 100% strain. A detailed thermographic analysis is employed to in situ image and characterize the AgNW network morphology during various stretched conditions. It is believed that this flexible, sandwich‐like, electrically conductive membrane is a good candidate for smart wearable devices and soft robots. Abstract : A preparation method to fabricate an elastic, stretchable, sandwich‐like electrically conductive membrane with low electric resistance (<0.1 (±0.01) Ω sq −1 ), low thermal diffusivity, and only minor changes in resistance upon stretching to 100% strain is shown.